Dermoscopy of Papular Epidermal Nevus with Skyline Basal Cell Layer. Issue 2 (23rd January 2017) - Balestri, Riccardo; Rizzoli, Laura; Rech, Giulia; Girardelli, Carlo Renè
Abstract: Papular epidermal nevus with skyline basal cell layer (PENS) is a newly described keratinocytic nevus whose dermoscopic characteristics have not been clarified. We used a dermatoscope to investigate the multiple PENSs of a patient with PENS syndrome. All the lesions shared a common dermoscopic homogeneous white pattern surrounded by peripheral, slightly dotted hyperpigmentation. The smallest lesions had no other features, whereas the largest lesions had some scaling, directly proportional to their dimension, and a central, clear, pink discoloration.